2021
DOI: 10.1016/j.jstrokecerebrovasdis.2021.105628
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Level of Physical Activity After Minor Stroke

Abstract: Objectives: To explore factors from the acute phase, and after three and 12 months, associated with level of self-reported physical activity 12 months after a minor ischemic stroke with National Institutes of Health Stroke Scale (NIHSS) score 3 in persons 70 years or younger. Materials and method: In this longitudinal cohort study patients were recruited consecutively from two stroke units. Activity level were measured with three sets of questions addressing the average number of frequency (times exercising ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…Overall, the study population had low physical activity levels, with approximately half of the participants being inactive. Among those who increased their physical activity, only a small number ( Figure 1 ) engaged in moderate- to vigorous-intensity exercise, which was a lower percentage than what has been reported in previous studies (approximately 40% active), 9 , 29 , 30 despite most participants experiencing a mild stroke. The decreaser group had a maximum decrease rate between 1 and 3 months and was followed by a plateau, which was consistent with results from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the study population had low physical activity levels, with approximately half of the participants being inactive. Among those who increased their physical activity, only a small number ( Figure 1 ) engaged in moderate- to vigorous-intensity exercise, which was a lower percentage than what has been reported in previous studies (approximately 40% active), 9 , 29 , 30 despite most participants experiencing a mild stroke. The decreaser group had a maximum decrease rate between 1 and 3 months and was followed by a plateau, which was consistent with results from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Fens et al., 2013; McHutchison et al., 2019) found that about 50% of patients with MIS showed a decline in their ability in daily work and to return to society, and about 40% of patients with MIS had cognitive dysfunction and communication difficulties. MIS is a type of stroke characterized by mild symptoms and short duration that rarely causes neurological deficits (Hamre et al., 2021), which are more likely to be overlooked. However, the higher incidence of PSCI in MIS patients would also bring serious harm to our society (Fens et al., 2013; McHutchison et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heavy burden of stroke mortality around the world, actions to prevent this neurological disorder are fundamental to the quality of life of the population. Among actions for stroke prevention, physical activity stands out in a preventive and therapeutic way in stroke survivors 4 . A systematic review with meta-analysis found 26 articles that analyzed the dose-response relationship between physical activity and stroke 5 .…”
Section: Introductionmentioning
confidence: 99%